Tasks Of The Rights And Obligations Of An Expert Accountant In The Process Of Conducting A Forensic Accounting Examination - Amonov, Amin (The American Journal of Management and Economics Innovations, 2021)
In the article the essence, legal-normal basics, designating necessity of judge-accounting expertise which is one type of expertise and formalization of its consequences were stated.